Proyectos Alianza Bioversity - CIAT: Software de Monitoreo y Refactorización de los Observatorios de Cultivos - Pedreros Pérez, Ricardo Andrés (2025)
This internship report presents the design and implementation of a digital monitoring platform for the CSICAP project and the refactoring of the Crop Observatories, developed in collaboration with the Alliance Bioversity International – CIAT. The system enhances agricultural data management through the integration of interoperable modules, improving the efficiency of data collection, analysis, and visualization within research and decision-making processes. This work supports the Alliance’s strategic goals under Lever 6 (Crops for Nutrition and Health) by strengthening digital infrastructures that enable sustainable and climate-resilient agri-food systems. Additionally, it contributes to the Digital Inclusion research theme by promoting open and accessible technological solutions that empower farmers, organizations, and public institutions to participate in evidence-based agro-environmental management and collaborative innovation.